Mental health status of Khon Kaen University students - Chatsantiprapa, Kannikar; Khamthanee, Chidchanok; Thepsuthammarat, Kaewjai (Asia-Pacific Journal of Science and Technology, 2017)
To screen for mental health and depression status among Khon Kaen University (KKU) students, a simple random sampling was used to obtain 312 students from 26,294 students in 17 faculties in the academic year 2010. A self-administered questionnaire containing independent variables, THMI-15 (Thai Mental Health Indicator), and PQH-2 (Patient Health Questionnaire) was used. The study found that KKU students had average mental health status in normal range with 15% (95%CI: 11.3, 19.5) in poor mental health and 21.5% (95%CI: 17.1, 26.5) in probable major depression. Depression in females (23.0%) was higher than in males (19.2%). The Art and Social group had the lowest mental health and the highest depression status. Failed parent’s marriage, insecure father’s occupation, inadequate monthly allowance, and study subject not the student’s own choice were significant factors for mental health status, whereas, the higher study year, insecure mother’s occupation, and inadequate monthly allowance were significant factors for depression status. Since inadequate monthly allowance was a common factor to both mental health and depression status, researchers advise that university authorities pay closest attention to this factor in particular. Those students having problems should be identified early by responsible staff, starting during enrollment, to prevent the risk of adverse consequences to the youths.